The role of HEXACO personality dimensions and emotion regulation in predicting depression - Mojgan Ansari Mahabadi; Amin Rafieipour; Khadijeh Abolmaali (Shahid Beheshti University of Medical Sciences, 2021)
Background: one of the main issues in the social health is investigating the factors affecting the quality of life of people with depression. The main objective of the present study was providing the trainings to help in improving the mental health and quality of life in people with depression for the counselors and psychologists. This study examined the role of HEXACO personality dimensions in predicting the quality of life with depression. Methods: The statistical population comprised all people with depression referred to counseling centers in Tehran mental hospitals, 200 subjects were chosen using simple random sampling. The BDI, HEXACO personality inventory, emotion regulation questionnaire, and SF-36 questionnaire for quality of life were used. The collected data were analyzed based on Pearson correlation coefficient and stepwise regression. Results: There was a positive and significant relationship between HEXACO personality dimensions and the quality of life in people suffering from depression. The results of stepwise regression analysis showed that all personality dimensions and emotion regulation could significantly predict the quality of life. Therefore, there was a positive and significant correlation between personality dimensions and emotion regulation with the quality of life. Conclusion: quality of life of people with depression can be predicted by emotion regulation and HEXACO personality factors.